1976
DOI: 10.1111/j.1469-1809.1976.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence study of Down's syndrome in Copenhagen, 1960–1971: with chromosome investigation

Abstract: The aim of the study was to obtain incidence figures for Down's syndrome throughout a period where a considerable change in the age distribution of child-bearing mothers has taken place and to study if the expected fall in incidence has occurred. In parts of the Copenhagen Metropolitan area 235 liveborn patients with Down's syndrome were ascertained in the period 1960 to 1971 in a population of 1-2 million with a total of 204771 births. All patients available were examined cytogenetically (75%). In 160 (90-4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Therefore, the newborn sex ratio in Lebanon does not seem to be higher than that of other white populations. Sex ratios for Down syndrome have varied in different studies, from 0.90 [22]to 1.35 [23]. The sex ratio of Down syndrome in our postnatal series is higher than that, for a sample size of n = 263.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the newborn sex ratio in Lebanon does not seem to be higher than that of other white populations. Sex ratios for Down syndrome have varied in different studies, from 0.90 [22]to 1.35 [23]. The sex ratio of Down syndrome in our postnatal series is higher than that, for a sample size of n = 263.…”
Section: Discussionmentioning
confidence: 80%
“…Some studies with nearly complete ascertainment have found a higher incidence of trisomy-21 in babies born to mothers less than 20 years of age when compared with mothers having an age of 20 to 29 years. 19 As regards paternal age (>25 years), it was also significantly associated with a group of congenital malformations (P<0.05). Though the adverse effects of paternal age on fetal development is fraught with controversies, some experts have highlighted the significant contributions of paternal age 20 and joint effect of parental age 21 to the development of congenital chromosomal syndromes.…”
Section: Discussionmentioning
confidence: 95%
“…Analysis showed that this increase was accounted for by the growing use of karyotyping to confirm the diagnosis. Among individuals with a clinical diagnosis only, sex ratio was 0.97 (1160 males/1198 females) [Collman & Stoller, 1962;Davidenkova et al, 1965;Huether, 1990;Kovaleva et al, 2001;Staples et al, 1991] while among individuals with confirmed trisomy 21 this figure was 1.31 (1918 males/1466 females) [Huether, 1990;Kovaleva et al, 2001;Mikkelsen et al, 1976;Mikkelsen et al, 1990;Sharav, 1991;Staples et al, 1991;Stoll et al, 1990;Wahrman & Fried, 1970]. Correspondingly, in samples where proportion of clinical diagnosis only was 30% and more, intermediate figure of 1.12 (1950 males/1742 females) [Baird & Sadovnik, 1987;Christoderescu et al, 1977;Johnson et al, 1996;Kallen et al, 1996;Kovaleva et al, 2001;Staples et al, 1991] was observed.…”
Section: Sex Ratio In Down Syndrome 431 Sex Ratio In Cases Considermentioning
confidence: 99%